(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The article discusses the relevance of introducing innovative methods in the process of teaching the Russian language to Uzbek philologists-Russianists. The question is raised that the main thing in teaching the Russian language is the functional principle of learning, and the communicative competence of students is put in the center of attention. It is said about the intensive search for new approaches, forms and innovative methods of teaching the Russian language, where the directive learning model is replaced by an interactive model that is more productive and focused on the personality of the student.